PROBLEM IN ASSESSING THE WEAR BEHAVIOUR OF CERAMICS: LOAD, TEMPERATURE AND ENVIRONMENTAL SENSITIVITY OF INDENTATION HARDNESS. - Czernuszka, J; Page, T (British Ceramic Soc, 1984)
The detailed microhardness behaviour of two debased alumina materials has been investigated. It has been established that microhardness is sensitive to the indentation load, temperature and environment. The substantial magnitude of these sensitivities is demonstrated and the implications for using indentation hardness as a wear parameter discussed.